Port Flow Simulation and In-cylinder Swirl Motion Characteristic Effects in Internal Combustion Engine Duty Cycle - Ikpe, Aniekan Essienubong; Owunna, Ikechukwu Bismarck; John, Philip Obhenime (Applications of Modelling and Simulation, 2021)
Combustion process in internal combustion engines involve significant temperature and pressure, carbon deposit, turbulence flame, swirling and tumbling flows which are considered necessary for operating these engines. This study examines the in-cylinder effects of swirling and tumbling motion along with the in-cylinder temperature during combustion process of air-fuel mixture. A detailed port flow analysis was carried out using ANSYS R-16 software and a valve lift of 8 mm. The velocity magnitude and mass flow rate were monitored using swirl motion simulated profiles and cut planes. Motion analysis was carried out to determine the angular velocity of the cycle using SOLIDWORKS 2017. The average angular velocity of the crankshaft was found to be 1315 rpm, with percentage deviation of less than 20%. It was also found that the area-weighted average velocity of charge was 11 m/s with corresponding mass flow rate measured as -0.055479 kg/s. The maximum flow rate was calculated at 8 mm as 0.005417 kg/s. The ICE swirl plane 1, 2 and 3 were characterized by different contours of velocity magnitude, indicating that the swirl intensity increased as the charge moved further down the cylinder while the charge volume of swirl increased along the cylinder length. For the ICE cut plane, the velocity increased as the swirl increased while the mass flow rate decreased as the fluid went further away from the poppet valve. Therefore, the intensity of swirl increased along the stroke length of the engine cylinder. In addition, increase in the swirl number led to uniform radial temperature distribution as well as reduction in the in-cylinder flame temperature which can mitigate against the formation of toxic pollutants.